Multiband Matched Bandstop Filter - Muhamad Hamzah, Siti Yuszaini; Ahmad, Badrul Hisham; Peng Wen, Wong (2010)
This paper is to propose a multiband matched bandstop filter. A lossy resonator is proposed and it demonstrates the concept and design of a perfectly matched bandstop filter with a matched response. . The design is based on a half wavelength (λ/2) and quarter wavelength (λ/4) resonator with gap coupling, parallel with an all-pass nominally-90º-phase-shift element, which can be optimized to achieve high Q-factor. The filter design is cascaded to achieve multiband isolation. Theoretical analysis together with experimental results are presented in this paper.